Clinical Insight into the Precaval Right Renal Artery: A Multidetector Row Computed Tomography Angiographic Study. (26th March 2013) - Srivastava, Shubha; Kumar, Indra; Babu, C. S. Ramesh; Gupta, K. K.; Gupta, O. P.
Abstract : Variations of course and number of renal vessels are not so uncommon and their knowledge is important for planning of minimally invasive renal surgeries. The earlier literature reports a prevalence of precaval right renal artery between 0.8% and 5%. Normally, the right renal artery passes posterior to the inferior vena cava, but it can also be precaval where it passes anterior to inferior vena cava. The multidetector row contrast enhanced computed tomography angiography allows precise evaluation of renal vasculature. The aim of this retrospective study is to determine the prevalence of precaval right renal artery. Amongst 73 MDCT scans studied, we identified 4 cases of precaval right renal artery with the prevalence being 5.48%, more than what is reported in the earlier literature. We also report a single and dominant precaval right renal artery in one of the cases, which is a rare finding. On the basis of these results, we conclude that precaval right renal artery appears to be more common and so the knowledge of this variant holds a major clinical implication in preventing misinterpretation of radiological images and proper planning of interventional procedures and minimally invasive surgeries.